USAHA MEMPERBAIKI KUALITAS GURU DENGAN MENGOPTIMALKAN KOMPETENSI PAEDAGOGIK DAN KOMPETENSI KEPRIBADIAN - admin admin; Khoiril khoiril (DIDAKTIKA, 2013)
One cause of low morale of our current generation is the low morale of teachers and parents. The tendency of the teacher's task is only to transfer of knowledge regardless of the moral values embodied in science. Learning conditions today are very oriented to the acquisition of the figures as the standardization of the quality of education. There are several factors that lead to teacher personality of "less alive" at this time, among other things: 1) The process of recruitment of teachers that emphasizes technical skills (hardskills) without regarding to the ability of non-technical (softskills) such as the ability to manage themselves and others not even a little educational institutions recruiting teacherswith no regard to both skills. 2) Education and training of teachers that only emphasize teachers' ability to master the curriculum, and 3) Do not understand the teaching profession as a professional vocation, meaning that the teacher is helping to develop others. It is time for teacher certification includes instrument / recording morals held by the teacher. The teacher's personality can be judged by the students and the community.